al-Furāt al-ausaṭ wa-’l-tiǧārah al-du- waliyah ḫilāl al-‘ahd al-bābilī al-qadīm - Кalīnkil, Hūrust
Klengel, Horst; The Middle Euphrates and International Trade during the Old Babylonian Period; ersch. 1986?; in Arabic, translated by Q?sim ?uwair.